Publishing in English or another language: An inclusive study of scholar’s language publication preferences in the natural, social and interdisciplinary sciences - Stockemer, Daniel; Wigginton, Michael J. (Université d'Ottawa | University of Ottawa, 2019)
To what extent has English become the dominant language of scientific communication? What factors push non-native speakers to publish their research in English rather than their native language? Using a survey of more than 800 authors of scientific papers in Springer Nature journals we find that the average non-anglophone researcher makes approximately 60% of their journal submissions in English. This percentage varies across disciplines, regions, and age groups, with younger scholars, Europeans, and those in the natural sciences favouring English more heavily. Finally, we find that the belief that publishing in English will increase the reputation of one’s work is a primary motivator; in contrast, perceived institutional pressures to publish in English do not seem to influence researchers’ language choice.
Keywords: Scientific communication; academic publishing; multilingual scholars; language of science; English as an international language